Población de la macrofauna edáfica detritívora como indicador biológico de la calidad de suelos en bosques sucesionales en Puerto Almendra, Loreto-Perú, 2017 - Cachique Murayari, Jerry James (2019)
In the present study, the population of the edaphic macro fauna in the forest successions of 1 year, 2 years, 7 years, 15 years and 40 years has been identified, quantified and classified by its functional activities, in the Center for Research and Teaching Forestry Puerto Almendras of the Faculty of Forestry Sciences of the UNAP in order to determine the level of soil quality. The methodology used was the one proposed by the International Tropical Soil Biology and Fertility Program (TSBF), which consists of subtracting monoliths from the soil 25 x 25 x 30 cm deep, which is divided into three strata with the help of a shovel: litter or mulch, 0 to 10 cm deep, 10 to 20 cm, and 20 to 30 cm. obtaining 3 repetitions randomly for each plot. The results obtained were the identification of 13 orders of macrofauna, among them are: Aranea, Hymenoptera, Isoptera, Hemiptera, Orthoptera, Coleoptera, Miriapodo, Isopoda, Opistoporos, Blattodea, Mantodea, pseudoscorpion and Tysanura. The ants stood out with 2533 ind/ m2, followed by termites with 1344 ind/m2. Regarding functional activities, the succession of "15 years" has the largest number of detritivore population, adding a total of 848 Ind/m2, it also presents the largest population of non-detritivores 944 Ind/m2, standing out the predators with 784 Ind/m2, Omnivores with 112 ind/m2 and herbivores with 48 ind/m2, obtaining the highest soil quality index 0.89, however, the quality level is low; located in the range of the index < 1.